Economics Education, Decision-Making, and Entrepreneurial Intention: A Mediation Analysis of Financial Literacy - Pashaei Azizeh; Hassani Mohammad; Mohajeran Behnaz; Shahbazi Kiumars (De Gruyter, 2024)
Adequate financial decision-making necessitates a solid foundation in financial literacy and comprehension of its principles. This is particularly crucial for students, as their financial and behavioral choices can significantly impact their future financial and career prospects. Consequently, the present study aimed to explore the causal links between economics education, financial literacy, decision-making abilities, and entrepreneurial intentions. Employing a descriptive-correlational approach, the researchers utilized structural equation modeling, drawing on a sample of 375 individuals purposefully selected from a population of 11,345 students at Urmia University. Data were collected through a questionnaire, and the research variables were initially assessed using multiple correspondence analysis. Subsequently, the research model was estimated. The findings revealed a positive and substantial impact of economics education on students' financial literacy and the influence of economics education on decision-making skills and entrepreneurial intentions through the mediating factor of financial literacy. Furthermore, the results confirmed the moderating role of socioeconomic status in the relationship between economics education and financial literacy. Consequently, the study's outcomes can inform educational institutions and policymakers, supporting the implementation of policies aimed at enhancing general economic education and emphasizing the equitable and distributive nature of such initiatives.